Respuestas

2014-03-06T00:59:12+01:00


despejamos "x"  :1) x= 27 - 6y
                                x= 3(9 - 2y)
                               2) x = 9 + 3y 
                                              7
                                    x = 3(3 + y) 
                                                 7

x=x
3(9 - 2y)=3(3 + y ) 
                       7
(9 - 2y)=(3 + y ) 
                   7
 7(9 - 2y)=(3 + y ) 
   63 - 14y= 3+y
             60 = 15y                   
               4=y

Ahora hallamos x
x= 27 - 6y
x= 27 - 6(4)
x= 3 


Espero haberte ayudado 
Suerteeee! :)